In search of the educational inspection: a brief review of the literature about its future - Cercós Soto, José (Avances en Supervisión Educativa, 2019)
A recent analysis (Lorenzo López Jordán, 2017) determines the precarious situation of the education inspection after the decentralisation process favoured by the development of the Spanish Constitution. Other analyses emphasise the distinct lack of literature describing what inspection should actually be like (Tomás Secadura, 2011), despite our continual questioning of who we are and what we do (Santiago Esteban, 2007). In this review we intend to reflect on that future by using already-produced information and by relating what inspection is to how education must be understood.
Keywords: education system, education inspection, autonomous region, assessment, future.